Exploring Andragogic Teaching Methods Used for Adult Learners (Sudurpaschim Spectrum, 2024)
Teaching adult learners presents unique challenges, as they bring diverse life experiences and prior knowledge to the classroom. Therefore, instructors must be well-versed in the fundamental principles of andragogy—the theory of adult learning. This study explores the experiences of university teachers in teaching adult learners and examines classroom practices in adult education settings at the university level. A qualitative research design was employed to collect and analyze data. Six university-level teachers were interviewed, and two classroom observations were conducted for each participant. Data were analyzed using thematic analysis, which included transcription, coding, and thematization. The findings revealed that most teachers primarily relied on lecture-based methods and demonstrated limited awareness of andragogical principles. Common classroom activities included explanation, question-and-answer sessions, and dictation of notes. Observations indicated that andragogical principles were largely absent in instructional practices. While a few participants reported incorporating learners' prior experiences into discussions, other key andragogical elements were notably overlooked. Based on these findings, it is suggested that the integration of andragogical principles in university teaching could enhance the effectiveness of adult learning. Reducing teacher talk time and increasing activities that foster critical thinking, problem-solving, and individualized instruction are recommended to improve student performance and engagement.